High Performance Maximum Power Point Tracking on Wind Energy Conversion System - Dwiana Hendrawati; Adi Soeprijanto; Mochamad Ashari (Institute of Advanced Engineering and Science, 2017)
This paper presents the maximum power point tracking (MPPT) to extract the power of wind energy conversion system (WECS) using the Firefly Algorithm (FA) algorithm. This paper aims to present the FA as one of the accurate algorithms in MPPT techniques. Recently, researchers tend to apply the MPPT digital technique with the P n O algorithm to track MPP. On the other hand, this Paper implements the FA included in the digital classification to improve the performance of the MPPT technique. Therefore, the FA tracking results are verified with P n O to show the accuracy of the MPPT algorithm. The results obtained show that performance is higher when using the FA algorithm